HIGH-YIELD PREPARATION OF ISOLATED RAT LIVER PARENCHYMAL CELLS : A Biochemical and Fine Structural Study - Berry, M. N. (The Rockefeller University Press, 1969)
A new technique employing continuous recirculating perfusion of the rat liver in situ, shaking of the liver in buffer in vitro, and filtration of the tissue through nylon mesh, results in the conversion of about 50% of the liver into intact, isolated parenchymal cells. The perfusion media consist of: (a) calcium-free Hanks' solution containing 0.05% collagenase and 0.10% hyaluronidase, and (b) magnesium and calcium-free Hanks' solution containing 2 mM ethylenediaminetetraacetate. Biochemical and morphologic studies indicate that the isolated cells are viable. They respire in a medium containing calcium ions, synthesize glucose from lactate, are impermeable to inulin, do not stain with trypan blue, and retain their structural integrity. Electron microscopy of biopsies taken during and after perfusion reveals that desmosomes are quickly cleaved. Hemidesmosome-containing areas of the cell membrane invaginate and appear to pinch off and migrate centrally. Tight and gap junctions, however, persist on the intact, isolated cells, retaining small segments of cytoplasm from formerly apposing parenchymal cells. Cells which do not retain tight and gap junctions display swelling of Golgi vacuoles and vacuoles in the peripheral cytoplasm. Cytoplasmic vacuolization in a small percentage of cells and potassium loss are the only indications of cell injury detected. By other parameters measured, the isolated cells are comparable to normal hepatic parenchymal cells in situ in appearance and function.